PERLINDUNGAN HUKUM HAK ANAK SEBAGAI KORBAN EKSPLOITASI EKONOMI DALAM PERSPEKTIF HUKUM PIDANA DI INDONESIA DIKAITKAN DENGAN HUKUM ISLAM - Rini, Devi Seftia; Firdaus, Emilda; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
By universal child has the human rights protected by law, even effectivesince the child in the womb Because they are entitled to legal protection for allthe activities that lead to growth and development in the future. Problems ofeconomic exploitation of children is influenced by poverty, lack of education,availability of employment, as well as the patriarchal culture. Based on the datafrom the Bureau of Criminal Investigation Police of the Republic of Indonesia in2011 to 2013 types pekejaan that exploits the Reviews largest commercial sexualexploitation of children as many as 205 cases, as many as 213 cases of economicexploitation.This type of research is a normative legal research writer. Normative legalresearch legal research is doctrinaire, Also Referred to as a research library orstudy documents dititk emphasis on secondary data. Data collection techniques inthis research is the study of literature, the author quotes from books, literature, orsupporting books Relating to the issues to be studied. In writing this essay, theauthor uses descriptive analysis (descriptive analisys) the which aims to provide adescription of the subject of the research is based on Data Obtained from thestudied subject.The results of this thesis research, legal protection for children can beinterpreted any attempt legal protection of the freedoms and rights of children aswell as the various interests related to child welfare. In Islam explained that Islamin protecting or maintaining the descent, not to get wasted, do didustakan and notfalsified. Received legal sanction perpetrators of economic exploitation ofchildren, shall be punished with Imprisonment of ten (10) years and / or a fine ofnot more Rp.200.000.000,00 (two hundred million rupiah). In Islamic law, if anact or prohibition is not stipulated in the legal provisions stipulated in the texts ofthe Quran and al-Hadith (had) the act or the legal prohibition stipulated in ta'zir.Suggestions in this thesis research, need to be made regulation more detailedregarding the protection of children as victims of economic exploitation, BecauseThe rights of children are robbed not necessarily be Returned so expect to be-ableto the make rules and services on the restoration of the rights of children afterbecoming victims of economic exploitation and the changes in the Law on theProtection of children in the provisions on sanctions has not changed.Keywords: Economic Exploitation - Children Protection – The Rights of Children